Rural regeneration through sustainable rural tourism development: A case study of Malaon village Gorakhpur, Uttar Pradesh - Anirudh Srivastav,; Sarvesh Kumar, (National Geographical Journal of India, 2025)
Rural regeneration encompasses a range of plans, policies, and actions aimed at the holistic development of rural areas. It involves the transformation of traditional rural practices to ensure sustainability while preserving rural identity in the context of a modernizing world. In contemporary society, an increasing number of people are turning to tourism as a means of relaxation and stress relief, which has brought rural tourism to the forefront of discussions on rural regeneration. Tourism, as a global industry, plays a significant role in the world economy and serves as a vital source of livelihood for many regions. Uttar Pradesh, having the highest number of villages in India, offers immense potential for the development of rural tourism. The United Nations World Tourism Organization (UNWTO) defines rural tourism as “a type of tourism activity in which the visitor’s experience is related to a wide range of products generally linked to nature-based activities, agriculture, rural lifestyle and culture, angling, and sightseeing.” Rural areas are characterized by clean and tranquil environments and possess a distinct ethnic essence. With their rich tangible and intangible cultural heritage and traditional agricultural practices, villages provide a strong foundation for the promotion of cultural and heritage tourism. The present study focuses on Malaon village, located in the Kauriram Block of Gorakhpur district, Uttar Pradesh. The village lies approximately 28 km south of the Gorakhpur district headquarters, 8 km from Kauriram, and 292 km from the state capital, Lucknow, and shares its northern boundary with the Rapti River. Malaon is renowned for its rich historical and cultural significance. Local traditions suggest that Gautam Buddha passed through the village during his journey from Sarnath, the site of his first sermon, to Kushinagar, where he attained Mahaparinirvana. The village is also historically associated with the eminent Indian philosopher, traveler, and Hindi scholar Rahul Sankrityayan. This paper examines the role of rural tourism in the process of rural regeneration by proposing strategies for the development of rural tourism and identifying areas with high potential for tourism growth. Additionally, it seeks to raise awareness about the preservation of village authenticity and to promote the empowerment of rural communities toward self-sufficiency and sustainable development.